Inter‐harmonic parameters estimation in power grid based on accelerated PSO and T5R11 window. Issue 6 (1st August 2019) - Xu, Yanchun; Du, Yufei; Li, Zhenhua; Lu, Mi
Abstract : A novel method on inter‐harmonic parameters estimation is proposed. It contains two steps: pre‐calculation and solution optimisation. An interpolated‐discrete fourier transform (DFT)‐based algorithm with a fifth‐order‐triangular and eleventh‐order‐rectangular (T5 R11 ) window is applied in the pre‐calculation process. Owing to mainlobe interferences caused by inter‐harmonics in the frequency domain, the accelerated particle swarm optimisation (PSO) algorithm is proposed to optimise the solution of pre‐calculation. Three aspects in the PSO are accelerated including utilising the especial DFT expression of T5 R11 window, applying a changing inertia weight and locking the frequency. From the view of estimating accuracy, the errors caused by spectral leakage can be restrained to a degree of 10 −11 by using T5 R11 window, and the relative errors of parameters could be optimised to a degree of 10 −5 at the tenth generation in the accelerated PSO. More simulations show that the proposed method can address many complex situations caused by inter‐harmonics, and corresponding detection accuracies satisfy the requirements of national and international standards.